2008
DOI: 10.2147/opth.s4668
|View full text |Cite
|
Sign up to set email alerts
|

Nonarteritic anterior ischemic optic neuropathy associated with chronic anemia: a case series of myelodysplastic syndrome patients

Abstract: Introduction:We report on three cases of visual loss due to nonarteritic anterior ischemic optic neuropathy that developed during the course of refractory anemia, a subtype of myelodysplastic syndrome.Patients and methods:Patients underwent fundus, visual field examination, and fluorescein angiography. A thrombophilic tendency investigation including prothrombin time, partial thromboplastin time, protein C, free protein S, and antithrombin III, polymerase chain reaction and hybridisation to allele-specific oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…However, little is known regarding optic neuritis associated with MDS. To the best of our knowledge, only a few reports have so far described optic neuritis in MDS (5,6). We herein report a rare case of optic neuritis which developed during the course of trisomy 8 MDS, with elevated eosinophils.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, little is known regarding optic neuritis associated with MDS. To the best of our knowledge, only a few reports have so far described optic neuritis in MDS (5,6). We herein report a rare case of optic neuritis which developed during the course of trisomy 8 MDS, with elevated eosinophils.…”
Section: Introductionmentioning
confidence: 75%
“…Kezuka et al examined the occurrence of optic complications in MDS patients and described optic neuritis in two of 41 patients with MDS (5). In addition, Brouzas et al reported a case series of three patients with MDS who had episodes of visual loss and in whom the diagnosis of optic neuropathy was established (6). They believed that chronic anemia due to MDS caused ischemic optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic vascular insufficiency of the optic nerve head is an important risk factor for the progressive form of normal tension glaucoma. 8 Chronic ischemic injury from low hemoglobin levels may lead to retinal ganglion cell layer thinning. An RNFL defect may develop from previous retinal hemorrhage in patients with hematologic malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…7 In a case report of 3 patients with myelodysplastic syndrome (MDS), the anemia subtype of MDS is likely to be involved in the initiation of NAION through a mechanism of anemic hypoxia and/or microvascular insufficiency. 8 If reduced oxygen delivery leads to NAION, chronic anemia may be a risk factor. The association between ischemic injury and ganglion cell loss has been investigated, 9 but the association between anemia and ganglion cell loss has not been examined.…”
mentioning
confidence: 99%
“…3). 8,9,[21][22][23][24][25][26][27][28][29][30][31][32][33] We also included our current case report for the final analysis, yielding a total of 19 patients.…”
Section: Study Selectionmentioning
confidence: 99%